The Role Of The Health Failure Mode And Effect Analysis (HFMEA) Method On The Quality Of Health Services In An Efforts To Improve Patient Safety - Asti Nurhyati; Anggie Annisa Permatasari; Erintya Ahsanin; Retno Tri Utami (Sean Institute, 2024)
safety is important because it is a system where hospitals make patient care safer. Patient safety is the foundation of good health care. Health workers' knowledge of patient safety includes proper patient identification, better communication, increased drug safety that needs to be considered, certainty of location, procedure, and proper operation for patients, reduction of infection risk, and risk of falls. But from a patient safety perspective, patient safety at various levels of health care is still poor worldwide and nationally. One of the most common adverse events in hospitals is patient falls. Worldwide, around 700,000 to 1 million patients fall in hospitals each year, causing around 250,000 injuries and up to 11,000 deaths. During hospitalization, around 2% of patients fall at least once. One of the international patient safety goals (IPSG) is to reduce the risk of patient falls. According to data from PERSI (Indonesian Hospital Association), the incidence of patient falls in Indonesia from January to September 2022 reached 14% of a total of 34 cases. This shows that the presentation of patient falls is included in the top 5 hospital medical incidents and is ranked second after medical errors. This shows a high rate of patient falls in Indonesia. The Hospital Patient Safety Committee (KKPRS) reported that the highest risk of patient falls in Indonesia occurred in the provinces of DKI Jakarta (37.9%), West Java (33.33%), Banten and Central Java (20%), Yogyakarta (13.8%), and East Java (3.33%). The purpose of this study was to determine the role of Health Failure Mode and Effect Analysis (HFMEA) on the quality of health services in an effort to improve patient safety, especially in hospitals